Service-oriented computing : 14th International Conference, ICSOC 2016, Banff, AB, Canada, October 10-13, 2016, Proceedings /: 14th International Conference, ICSOC 2016, Banff, AB, Canada, October 10-13, 2016, Proceedings. (2016) - Unknown
No abstract available